2009
DOI: 10.2214/ajr.09.2631
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Arteriovenous Fistulas

Abstract: Familiarity with the spectrum of imaging findings in AVFs is essential for the accurate interpretation of images and facilitates diagnosis and therapeutic management. Radiologists can play a critical role in the diagnosis and treatment of AVFs. Digital angiography is helpful in elaborating a vascular map for endovascular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 30 publications
0
22
0
7
Order By: Relevance
“…[6] AVFs are classified as being congenital or acquired. Congenital AVFs (arteriovenous malformations) typically occur as a result of failure of differentiation between an artery and vein during embryology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] AVFs are classified as being congenital or acquired. Congenital AVFs (arteriovenous malformations) typically occur as a result of failure of differentiation between an artery and vein during embryology.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Acquired AVFs can be the result of trauma, neoplasm, erosion of an arterial aneurysm or surgically created hemodialysis fistulas. [6] Penetrating trauma has been reported as the most common cause of acquired traumatic AVFs, accounting for 3% of all vascular injuries. Acquired AVFs generally demonstrate one large feeding artery and one large draining vein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To standardize the process of reporting breast masses, the American College of Radiology instituted the Breast Imaging Reporting and Data System (BI‐RADS) in 2003 2 , 3 . Subsequently, several authors demonstrated that the BI‐RADS features of margin, shape, orientation, lesion boundary, echo pattern, and posterior acoustic attenuation were significantly different for malignant and benign masses 4 .…”
mentioning
confidence: 99%
“…In this case, localization could indicate possible origin from the testicular artery, but the history and clinical evaluation alone did not provide any information that allowed identification of the origin of the fistula. Typically, the clinical presentation (including signs of high‐output cardiac failure and an asymptomatic pulsatile abdominal mass) has been reported in 20–50% of human patients diagnosed with AVF 3, 4, 5. Origin, size, localization, and evolution time of the fistula determine the degree of hemodynamic disturbances.…”
mentioning
confidence: 99%